Evaluation of Certain Pharmaceutical Quality Attributes of Lisinopril Split Tablets - Khairi M. S. Fahelelbom; Moawia M. M. Al-Tabakha; Nermin A. M. Eissa; Jeevani Javadi (MDPI AG, 2016)
Tablet splitting is an accepted practice for the administration of drugs for a variety of reasons, including dose adjustment, ease of swallowing and cost savings. The purpose of this study was to evaluate the physical properties of lisinopril tablets as a result of splitting the tablets either by hand or with a splitting device. The impact of the splitting technique of lisinopril (Zestril® tablets, 20 mg) on certain physical parameters such as weight variation, friability, disintegration, dissolution and drug content were studied. Splitting the tablets either by hand or with a splitter resulted in a minute but statistically significant average weight loss of <0.25% of the tablet to the surrounding environment. The variability in the weight of the hand-split tablet halves was more pronounced (37 out of 40 tablet halves varied by more than 10% from the mean weight) than when using the tablet splitter (3 out of 40 tablet halves). The dissolution and drug content of the hand-split tablets were therefore affected because of weight differences. However, the pharmacopoeia requirements for friability and disintegration time were met. Hand splitting of tablets can result in an inaccurate dose and may present clinical safety issues, especially for drugs with a narrow therapeutic window in which large fluctuations in drug concentrations are undesirable. It is recommended to use tablets with the exact desired dose, but if this is not an option, then a tablet splitter could be used.